The Relationship between Left Ventricular Diastolic Function Parameters and Coronary Artery Disease Severity - Khadije Mohammadi; Mohammad Masoomi; Mahsa Akrami; Shirin Habibi Khorasani; Mina Moridi; Sara Saidi (Iranian Journal of Medical Sciences)
Background: The relationship between diastolic function parameters and the severity of coronary artery disease (CAD) is controversial. This study aimed to determine the relationship between left ventricular diastolic function and the severity of CAD.Methods: This cross-sectional study included 63 patients with Ischemic heart disease (IHD) or those suspected of having IHD, who underwent angiography. The study was conducted in Shafa Hospital, Kerman, Iran, from 2021 to 2022. Two-dimensional (2D) strain echocardiography was used to assess left ventricular (LV) function parameters, followed by coronary angiography. Based on the severity of the disease, patients with significant CAD were placed in the case group, and patients with insignificant CAD were placed in the control group. The correlation between the CAD severity and the severity of LV diastolic dysfunction was computed. Descriptive tests, independent t tests, and Spearman correlation coefficients were used. P<0.05 was considered statistically significant.Results: The results indicated that there was no correlation between E/e′ (P=0.103), left atrial volume index (LAVI) (P=0.168), tricuspid regurgitation velocity (TRV) (P=0.217), myocardial performance index (MPI) (P=0.106), E wave deceleration time (dt) (P=0.644), and late diastolic strain rate (P=0.502) with CAD severity based on SYNTAX score. However, there was a correlation between left atrial (LA) strain (P=0.017), global longitudinal strain (GLS) (P<0.001), early diastolic strain rate (P<0.001), and systolic strain rate (P=0.047) with SYNTAX score. Besides, there was a correlation between LA strain (P=0.017), GLS (P<0.001), early diastolic strain rate (P<0.001), and late diastolic strain rate (P=0.035) with numbers of epicardial coronary arteries with significant lesions.Conclusion: In contrast with 2D strain echocardiography, this study showed that conventional echocardiography parameters had no significant relationship with CAD severity. GLS had the strongest correlation with CAD severity, and diastolic strain rates had a weaker correlation with CAD severity.